Valuation Methods of Interest Rate Options - Pumprová, Zuzana; Málek, Jiří, 1953-; Baran, Jaroslav; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2011)
The subject of this thesis are selected interest rate models and valuation of interest rate derivatives, especially interest rate options. Time-homogeneous one-factor short rate models, Vasicek and Cox-Ingersoll-Ross, and time-inhomogeneous short rate model, Hull{White, are treated. Heath-Jarrow-Morton framework is introduced as an alternative to short rate models, evolving the entire term structure of interest rates. The short rate models are shown to be special cases of models within the framework. The models are derived using the risk-neutral pricing methodology.
Vedoucí práce: Jiří Málek
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2011
Rok obhajoby 2011
Keywords: finance [obor dipl. práce]; diplomové práce; master's theses